China rises : [videorecording (DVD)] : a documentary in four parts - Murphy, Michael (Discovery Channel : Distributed exclusively by Image Entertainment, 2008)
China Rises (a look at this rapidly developing economic power, from a factory to a pop concert and an Olympic volleyball court to the red carpet at the Shanghai Film Festival) and Behind the Great Wall (a look at the world's single greatest structure).